2022
DOI: 10.4314/eajess.v3i4.200
|View full text |Cite
|
Sign up to set email alerts
|

Uses of Authentic Assessment Tools: Implications towards Competence Acquisition among Undergraduate Prospective Science Teachers in Tanzania

Abstract: The study was concerned with the uses of authentic assessment tools in higher education institutions, particularly portfolios and practical work. The study employed the mixed method research approach with the explanatory sequential research design. The sample for the study involved 231 third year undergraduate prospective science teachers who were selected randomly and 6 instructors who were purposively selected from two higher learning institutions. Data was collected by using a questionnaire and a semi-struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Several studies have indicated uses of authentic assessment on summative basis (Broadbent et al, 2018;Hilden et al, 2022;Houston & Thompson, 2017;Ishaq et al, 2020;Nyinge, 2022;Sewagegn & Diale, 2020). For instance, Hilden et al (2022) insisted on the summative use of authentic assessment since instructor are confident in their uses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated uses of authentic assessment on summative basis (Broadbent et al, 2018;Hilden et al, 2022;Houston & Thompson, 2017;Ishaq et al, 2020;Nyinge, 2022;Sewagegn & Diale, 2020). For instance, Hilden et al (2022) insisted on the summative use of authentic assessment since instructor are confident in their uses.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Bloxham and Boyd (2007) comment that authentic assessment are used for the sake of grading and certification due to modularization system of higher education institutions. Similarly, Nyinge (2022) indicated some authentic assessment tools namely practical work, projects and portfolios to be used summatively. However, little is known on the formative use of authentic assessment in HEIs.…”
Section: Introductionmentioning
confidence: 99%